Realizing nursing: a multimodal biopsychopharmacosocial approach to psychiatric nursing. Issue 6 (1st May 2014) - Clark, L. L.; Clarke, T.
Abstract : Accessible summary: This paper describes a person‐centred approach to psychiatric nursing assessment. The biopsychopharmacosocial (BPPS) approach builds on previous models and best practice to promote person‐centred care planning. The approach minimizes the risk of aspects of the person's condition being ignored or inappropriately attributed to a previously diagnosed medical or psychiatric condition (diagnostic overshadowing). The BPPS approach structures and guides person‐centred nursing assessment, formulation and care planning, and will be most effective when supported by expert nurses and clinical academics. Abstract: The biological and psychosocial components of health, illness and treatment are well recognized. In addition, pharmacological interventions interact with both these components regarding health and illness; all components are potentially modifiable. A better understanding of these interactions on the course of illness, especially at the interface between illness and treatment, is needed to guide effective clinical and psychiatric nursing interventions. To this end, a multimodal biopsychopharmacosocial approach to assessment, formulation, care planning and implementation by psychiatric nurses is proposed. It is argued that a biopsychopharmacosocial approach, including a multimodal functional element, provides a person‐centred, responsive and responsible basis for a comprehensive approach to practice. The use of this approach will improve intervention outcomes and contribute to the ongoing development of psychiatric nursing practice. It is suggested that, in part, this will be achieved through innovative teaching methods delivered by 'expert nurses' and clinical academics.